1984
DOI: 10.1111/j.1532-5415.1984.tb05151.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Training for Medical and Nursing Students: Learning to Collaborate in the Care of Geriatric Patients

Abstract: A medicine clerkship for students at the Albert Einstein College of Medicine provided the setting for a pilot program in interdisciplinary geriatric training with nursing students from the College of Mount Saint Vincent. The program's objectives were to provide opportunities for interdisciplinary collaboration and to increase appreciation for the role of each discipline in caring for the aged. Additionally, it sought to foster a holistic approach to the aging and a recognition of the psychosocial influences on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…On inspection by the second reviewer, 6 of these were subsequently excluded, resulting in 13 articles included in the final review (Table 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] Two studies from the same group employed the same intervention and evaluation methods to medical and social work students, and medical and nursing students, respectively. 27,28 Two other studies did not report results but were included to provide a more complete description of study designs, interventions, and measurement methods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On inspection by the second reviewer, 6 of these were subsequently excluded, resulting in 13 articles included in the final review (Table 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] Two studies from the same group employed the same intervention and evaluation methods to medical and social work students, and medical and nursing students, respectively. 27,28 Two other studies did not report results but were included to provide a more complete description of study designs, interventions, and measurement methods.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies developed their own questionnaires and described some of their features (eg, number of items, response scales). 25,30,32,33,35 Of these 5, 2 studies reported measurements of survey reliability or validity. 32,35 The instruments used in the remaining 4 studies 26,28,34 were not described.…”
Section: 35mentioning
confidence: 99%
See 3 more Smart Citations